2022
DOI: 10.3390/microorganisms10081486
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of Malnutrition on the Gut Microbiota–Brain Axis the Core Pathologies of Anorexia Nervosa?

Abstract: Anorexia nervosa (AN) is a disabling, costly, and potentially deadly illness. Treatment failure and relapse after treatment are common. Several studies have indicated the involvement of the gut microbiota–brain (GMB) axis. This narrative review hypothesizes that AN is driven by malnutrition-induced alterations in the GMB axis in susceptible individuals. According to this hypothesis, initial weight loss can voluntarily occur through dieting or be caused by somatic or psychiatric diseases. Malnutrition-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 116 publications
(209 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, UR may impact the composition of the gut microbiota, which has been implicated in neurological health. Changes in gut microbiota have been linked to inflammation, oxidative stress, and immune dysfunction, which may contribute to the development of severe neurological deficits in ISS at UR [ 23 ]. Therefore, early identification and management of UR in this population may be a critical intervention in improving neurological outcomes and overall health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, UR may impact the composition of the gut microbiota, which has been implicated in neurological health. Changes in gut microbiota have been linked to inflammation, oxidative stress, and immune dysfunction, which may contribute to the development of severe neurological deficits in ISS at UR [ 23 ]. Therefore, early identification and management of UR in this population may be a critical intervention in improving neurological outcomes and overall health.…”
Section: Discussionmentioning
confidence: 99%
“…AN shows significant heritability as family studies have shown a substantial prevalence of AN in the first-degree relatives of a proband, who are about 11 times more likely to develop AN than controls [13]. Many concepts have been suggested by different scientists to explain and understand how AN is developed and maintained [14].…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%
“…These authors claim that a dysbiosis involving an increase in these bacteria would cause the segregation of ClpB affecting the aetiology of AN either by (a) a direct effect on the peripheral satiety routes -increasing PYY [ 25 , 26 ], or centrally through MC4R [ 27 ]; or (b) an indirect effect from the formation of anti-ClpB IgG antibodies cross-reactive with α-MSH that would form immune complexes, activating chronically the central MC4R receptor and inducing increased satiety and anxiety, or both. Recently, Frostad [ 28 ] has emphasized the role of CCK-4 as a complementary mechanism integrated into this model; malnutrition would cause disruption of the blood–brain barrier, increasing the sensitivity of CCK2 receptors to the CCK-4 peptide generated by enteroendocrine I cells during meals. Thus, anticipatory anxiety would occur that would favour psychological maintenance mechanisms such as the pursuit of thinness and weight overvaluation.…”
Section: Introductionmentioning
confidence: 99%